2018
DOI: 10.4067/s0717-95022018000401453
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of Vascular Endothelial Growth Factor, β-cell Lymphoma 2 and Cluster of Differentiation 68 in Cerebellar Tissue of Rats Treated with Ganoderma lucidum

Abstract: Traumatic brain injury (TBI) can potentially lead to hemorrhages in all areas of the skull, which can damage cells and nerve connections. This study aims to investigate the protective effects of Ganoderma lucidum polysaccharides (GLPS) as a antioxidant on cerebellar cell tissues after traumatic brain injury in rats. Sprague Dawley rats were subjected to TBI with a weight-drop device using 300 g-1m weight-height impact. The groups are consisted of control, trauma, and trauma+Ganoderma lucidum groups. At seven d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Application of inclusion and exclusion criteria to titles and abstracts of search resulted in 201 full‐text articles that were screened for eligibility; 43 journal articles (Bailes & Mills, 2010; Cheng et al., 2016; Cole et al., 2010; Davis et al., 2008; Deng‐Bryant et al., 2011; Elliott et al., 2018; Gerbatin et al., 2019; Greco et al., 2016; Hu, Wang, Jin, et al., 2009; Hu, Wang, Qiao, et al., 2009; Itoh et al., 2013; Ji et al., 2017; Jiang et al., 2017; Krishna et al., 2019; Kumar et al., 2014; Lim et al., 2013; Liu et al., 2017; Mills et al., 2011; Ozbal et al., 2015; Özevren et al., 2018; Prins et al., 2005; Prins & Hovda, 2009; Rubovitch et al., 2019; Saraiva et al., 2012; Schober et al., 2016; Schwartzkroin et al., 2010; Sharma et al., 2010; Shin & Dixon, 2011; Su et al., 2016; Thau‐Zuchman et al., 2019; Toklu et al., 2009; Wang et al., 2018; Wang, Li, et al., 2016; Wang, Zhang, et al, 2016; Wei et al., 2015; Wu et al., 2011, 2014; Xie et al., 2018; Xing et al., 2016; Xu et al., 2017; Zhang et al, 2018; Zhao et al., 2014; Zhu et al., 2017) met all eligibility criteria. Most studies (28/43) were conducted since 2013, with four to seven new studies being released each year since 2016.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Application of inclusion and exclusion criteria to titles and abstracts of search resulted in 201 full‐text articles that were screened for eligibility; 43 journal articles (Bailes & Mills, 2010; Cheng et al., 2016; Cole et al., 2010; Davis et al., 2008; Deng‐Bryant et al., 2011; Elliott et al., 2018; Gerbatin et al., 2019; Greco et al., 2016; Hu, Wang, Jin, et al., 2009; Hu, Wang, Qiao, et al., 2009; Itoh et al., 2013; Ji et al., 2017; Jiang et al., 2017; Krishna et al., 2019; Kumar et al., 2014; Lim et al., 2013; Liu et al., 2017; Mills et al., 2011; Ozbal et al., 2015; Özevren et al., 2018; Prins et al., 2005; Prins & Hovda, 2009; Rubovitch et al., 2019; Saraiva et al., 2012; Schober et al., 2016; Schwartzkroin et al., 2010; Sharma et al., 2010; Shin & Dixon, 2011; Su et al., 2016; Thau‐Zuchman et al., 2019; Toklu et al., 2009; Wang et al., 2018; Wang, Li, et al., 2016; Wang, Zhang, et al, 2016; Wei et al., 2015; Wu et al., 2011, 2014; Xie et al., 2018; Xing et al., 2016; Xu et al., 2017; Zhang et al, 2018; Zhao et al., 2014; Zhu et al., 2017) met all eligibility criteria. Most studies (28/43) were conducted since 2013, with four to seven new studies being released each year since 2016.…”
Section: Resultsmentioning
confidence: 99%
“… natural compounds with known anti‐oxidant properties (Cheng et al., 2016; Itoh et al., 2013; Ji et al., 2017; Jiang et al., 2017; Krishna et al., 2019; Ozbal et al., 2015; Toklu et al., 2009; Wei et al., 2015); branched chain amino acids (BCAA) (Cole et al., 2010; Elliott et al., 2018; Lim et al., 2013); creatine (Gerbatin et al., 2019; Saraiva et al., 2012); fasting and caloric restriction (Davis et al., 2008; Liu et al., 2017; Rubovitch et al., 2019); KD (Deng‐Bryant et al., 2011; Greco et al., 2016; Hu, Wang, Jin, et al., 2009; Hu, Wang, Qiao, et al., 2009; Prins et al., 2005; Prins & Hovda, 2009; Schwartzkroin et al., 2010; Zhang et al., 2018); multi‐supplements (Thau‐Zuchman et al., 2019; Wu et al., 2014); ω‐3 polyunsaturated fatty acids (PUFAs) (Bailes & Mills, 2010; Mills et al., 2011; Schober et al., 2016; Shin & Dixon, 2011; Su et al., 2016; Wu et al., 2011; Zhu et al., 2017); or natural compounds used in traditional eastern medicine (Kumar et al., 2014; Özevren et al., 2018; Sharma et al., 2010; Wang et al., 2018; Wang, Fan, et al, 2016; Wang, Zhang, et al, 2016; Xie et al., 2018; Xing et al., 2016; Zhao et al., 2014). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Özevren et al demonstrated that G. lucidum treatment after brain injury could be an alternative treatment to decrease inflammation and oedema, preventing neuronal and glial cell degeneration with analyses of p38 mitogen-activated protein kinase, vascular endothelial growth factor, and cluster of differentiation 68 expression levels 38 . Another study by Özevren et al 39 . on rats with traumatic brain injury showed that G. lucidum polysaccharides may play a certain role for expression of apoptosis-associated proteins and, in this way, have neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%